Plasma atomic layer etching of molybdenum with surface fluorination - Kim, Yongjae; Kang, Hojin; Ha, Heeju; Kim, Changkoo; Cho, Sungmin; Chae, Heeyeop (Applied Surface Science, 2023)
This work developed a plasma atomic layer etching (ALE) process for molybdenum (Mo) with surface fluorination and ion bombardment. The Mo surface was fluorinated with CHF3 or C4F8 plasmas, and the fluorinated surface was etched by Ar plasma. The fluorocarbon layers were generated with two fluorocarbon sources of CHF3 or C4F8 plasmas on the Mo surfaces. C4F8 plasma generates more fluorine-rich fluorocarbons than CHF3 plasma. The etch per cycle (EPC) of Mo was determined to be 0.8 nm/cycle for CHF3 plasma and 2.8 nm/cycle for C4F8 plasma in the ALE window region. The dependence of the EPC of Mo on the ion energy in the etching step was investigated, and an ALE window was observed in the energy range of 100–225 V. The EPC of Mo increases with increasing Ar plasma time and saturates at 150 s for the CHF3 plasma and 420 s for the C4F8 plasma. Fluorine residue after ALE was as low as 4%, which is lower than radical etching and RIE. The surface roughness was measured at 0.37 nm with the ALE process, which is lower than radical etching and RIE processes.
Keywords: Ar plasmas; Atomic layer etching; Etch residue; Etching process; Molybdenum; Radical etching; Reactive ion etching; Reactive-ion etching; Surface fluorination; Atomic layer etching (ALE); Etch residue; Molybdenum (Mo); Radical etching; Reactive ion etching (RIE); Surface roughness